Mapping Pre-Service Physics Teachers’ Research-Review Competence Using Rasch Person-Criterion Targeting - Abdurrahman Abdurrahman; Alwielland Q. Bello; Fadiyah Farah Khoirunnisa; Abdurrahman; Alwielland Q. Bello; Fadiyah Farah Khoirunnisa; Novinta Nurulsari; Agus Suyatna; Novinta Nurulsari; Agus Suyatna (Universitas Negeri Malang, 2026)
Pre-service physics teachers are increasingly expected to engage with educational research as a basis for professional judgement. This study examined their research-review competence using a rubric-scored article critique and Rasch measurement. Two intact third-year cohorts at a state university in Lampung, Indonesia completed the same critique prompts after identical instructional preparation but reviewed different article types. Class A critiqued a qualitative article and Class B critiqued a quantitative article. Written critiques were scored on a nine-criterion rubric with a shared four-point rating scale and analysed using the Rasch Rating Scale Model in Winsteps. The rubric showed adequate measurement quality for diagnostic interpretation and produced a coherent criterion difficulty hierarchy across cohorts. Person-criterion targeting using Wright maps indicated that critique of introductory framing was the most consistently demanding component in both article types. Secondary high-demand components differed by task. The qualitative critique concentrated difficulty on evidence-claim evaluation, methodological critique, and coherence of argumentation, whereas the quantitative critique concentrated difficulty on academic writing and citation practice, evidence-claim evaluation, and critique of implications, limitations, and potential bias. These findings show how Rasch targeting can move beyond total scores to identify priority components for strengthening research-critique competence in teacher education.